1997
DOI: 10.1890/0012-9658(1997)078[1494:bcittl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bird Communities in Transition: The Lago Guri Islands

Abstract: We report on the bird communities of a set of 12 7‐yr‐old forested land‐bridge islands in Lago Guri, a 4300 km2 hydroelectric impoundment in the State of Bolivar, Venezuela. Birds were censused on all islands and at mainland control sites by spot mapping in 1993, and via point counts in 1995. Instead of orderly “nested sets” of species on landmasses of graded size, the species composition of small (≈1 ha) and medium (11–12 ha) islands was highly variable. Spot mapping substantiated the occurrence of 58 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 28 publications
0
72
0
1
Order By: Relevance
“…Population-and assemblage-level responses in low-contrast systems have been examined mainly for plants, birds, and rodents (e.g. Adler & Seamon, 1991;Leigh et al, 1993;Terborgh et al, 1997;Asquith & Mejia-Chang, 2005). For bats, on the other hand, nearly all studies on fragmentation effects save those of Cosson et al (1999) and have been conducted in rather young, low-contrast systems sensu Watson (2002) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Population-and assemblage-level responses in low-contrast systems have been examined mainly for plants, birds, and rodents (e.g. Adler & Seamon, 1991;Leigh et al, 1993;Terborgh et al, 1997;Asquith & Mejia-Chang, 2005). For bats, on the other hand, nearly all studies on fragmentation effects save those of Cosson et al (1999) and have been conducted in rather young, low-contrast systems sensu Watson (2002) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On Barro Colorado Island, Panama, high avian nest predation has been attributed in part to increased small mammalian nest predators such as white-nosed coatimundi (Nasua narica), whitefaced capuchin monkeys (Cebus capucinus), and opossums following isolation from the mainland, and subsequent loss of large carnivores, when the Panama Canal was built (Loiselle & Hoppes, 1983;Sieving, 1992;Wright et al, 1994). On the Lago Guri islands in Venezuela, former hilltops isolated from nearby mainland by a hydro-electric reservoir, anomalously low bird densities were associated with abundant olive capuchin monkeys (Cebus olivaceus), which depredated all artificial nests (Terborgh et al, 1997). Olive baboons (Papio anubis) also dramatically increased in Ghana following steep declines in lions (Pantera leo) and leopards (Pantera pardus), negatively impacting smaller ungulates, primates, rodents, and birds, as well as human livestock, pets, and crops (Brashares et al, 2010).…”
Section: Indirect Effects Of Fragmentation: Trophic Cascadesmentioning
confidence: 99%
“…This altered nutrient regime drove a ricocheting bottom-up effect, in which the positive indirect effects of howler monkey density (and concomitant increased nutrient availability) on bird species richness exceeded the negative, direct effects of island area on bird species richness (Feeley & Terborgh, 2008). Indeed, birds maintained territories 3 to 5 times smaller on islands with abundant howler monkeys than on the adjacent mainland (Terborgh et al, 1997). While the herbivore hyperdensities are commonly attributed to the absence of all large and mid-sized predators from the islands (Terborgh et al, 2001(Terborgh et al, , 2006, the very small size of the islands, extensive edge effects, and refuge effect during reservoir inundation also likely contributed (S.J.…”
Section: Mesoherbivore Releasementioning
confidence: 99%
“…Egg predation was observed for various species of capuchin monkeys, such as Sapajus apella, Cebus capucinus, C. albifrons and C. olivaceus Boinski 1992, Riehl andJara 2009). Moreover, studies with artificial nests have revealed high rates of egg predation in habitat islands harbouring capuchins (Terborgh et al 1997). In Costa Rica, Cebus capucinus are known to regularly search for nests during the nesting seasons, and to feed on eggs of many species of birds (Fedigan 1990).…”
Section: Introductionmentioning
confidence: 99%